Multilevel Fully Integrated Electromechanical Property Modulation of Functionally Graded Graphene‐Reinforced Piezoelectric Actuators: Coupled Effect of Poling Orientation. Issue 4 (3rd February 2023) - Singh, Kamalpreet; Shingare, Kishor Balasaheb; Mukhopadhyay, Tanmoy; Naskar, Susmita
Abstract: This article explores the coupled static and dynamic electromechanical responses of single and multilayered functionally graded (FG) graphene platelet (GPL)‐reinforced piezoelectric composite (GRPC) plates by developing a 3D finite‐element model. The bending and eigenfrequency of piezoelectric FG composite plates are investigated, wherein an active behavior is proposed to be exploited in terms of the functional design of poling angle for a more elementary level property modulation. The numerical results reveal that the mechanical behavior concerning deflection and resonance frequency of FG‐GRPC plates can be significantly enhanced and modulated due to the influence of piezoelectricity and a small fraction of GPLs along with the consideration of poling angle in a multiscale fully integrated computational framework. The notions of on‐demand property modulation, actuation, and active control are established here by undertaking a comprehensive numerical analysis considering the coupled influences of poling orientations, different distributions, patterns, and weight fractions of GPLs along with different electromechanical loadings. Against the backdrop of the recent advances in microscale manufacturing, the current computational work will provide necessary physical insights in modeling piezoelectric multifunctional FG composites for active control of mechanical properties and harvesting electromechanical energy in a range of devices and systems. Abstract : This article explores the coupled static and dynamic electromechanical responses of functionally graded graphene platelet (GPL)‐reinforced piezoelectric composite plates. The notions of on‐demand property modulation, actuation, and active control are established by undertaking a comprehensive numerical analysis considering the coupled influences of poling orientations, different distributions, patterns, stacking layers, and weight fractions of GPLs along with different electromechanical loadings.